A health service for the nation (London : published by the Women Public Health Officers' Association)
1943-03-27 1943 1940s 8 pages 26. Even in small villages, we believe that two rooms with a separate entrance, added to the school buildings (and many village schools are ripe for re-building) would provide an adequate Health Centre, the various health services, including that of the Home Doctor, being found there in rotation ; for certain forms of Medical and Dental Treatment a mobile unit may be useful. In no circumstances should a doctor's private surgery be designated a Health Centre. In rural areas, the staff of Health Visitors should be numerous enough to enable a Health Visitor to make a weekly visit to each village Health Centre. STAFFING OF HEALTH CENTRES. 27. (a) MEDICAL. We believe that the specialised medical staff should be common to both branches of the new National Health Service, and that the Home Doctors working at the Health Centres should refer their patients for further advice and treatment either to the Divisional Treatment Centre or to the Regional Hospital. We strongly deprecate the suggestion made in the Draft Interim Report of the Planning Commission that Home Doctors, ie., general practitioners working in the Health Centres, should assume responsibility for ante-natal, post-natal, and infant welfare sessions. We believe that these services require a greater degree of specialised knowledge and experience than can reasonably be expected of many general practitioners and we believe that the success and popularity of these existing services is largely due to the confidence which the mothers have in the specialised medical staff now normally in charge of these services. (b) HEALTH VISITORS. Health visitors should continue to perform their present duties in the future. The work of Health Visitors may well include the duties in the school and homes of school children now performed by School Nurses. They should also administer the Home Helps service. They should work in and from the Health Centres, in numbers varying with the population served by the Centre. In each Centre it should be possible for an individual Health Visitor to see mothers in privacy. (c) MUNICIPAL MIDWIVES would use the Health Centres for interviewing their patients and would attend ante-natal sessions when practicable. (d) CLERICAL STAFF. This should be adequate to deal with the Health Records and Health Centre correspondence concerning all persons living in the district served by the Health Centre. (e) SANITARY INSPECTORS. In large towns it might economise travelling time and encourage co-operation if an office for the District Sanitary or Housing Inspector, whether man or woman, was provided in some or all of the Health Centres. Six 292/847/2/155